Relationship between job stress, quality of working life and turnover intention among house officers in Malaysia - Wan Zulkifle, Wan Zahidah; Alias, Intan Aidura (2018)
The number of house officers leaving medical practice in Malaysia is alarming. In 2015, it was stated that 1 out of 5 house officers were not able to complete their housemanship training. Although several interventions had been taken to improve the housemanship system, the numbers of turnover showed that the problems have not been managed effectively. Studies have revealed that job stress strongly predicts turnover intention. Job satisfaction and quality of working life have been proposed to mediate this relationship. Many evidences are available for the job satisfaction but few for quality of working life. The present study therefore intends to examine the relationship between job stress and turnover intention, and how quality of working life mediate this relationship among house officers in Malaysia. Using a cross-sectional study design, a four-segment questionnaire assessing demographics, job stress, quality of working life and turnover intention will be administered via online to 500 house officers across Malaysia. The measures to be used are Occupational Stress Scale, Quality of Working Life questionnaire and Turnover Intention Scale. Regression analysis will be carried out to test the mediating effect of quality of working life on the relationship between job stress and turnover intention. The study will be beneficial to understand the factors that are associated with high turnover among house officers, thus assisting in planning interventions to reduce further loss of human capital.